1994
DOI: 10.1111/j.1467-9396.1994.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

The Differential‐Productivity Hypothesis and Purchasing‐Power Parties: Some New Evidence*

Abstract: The structure of prices of goods entering into international trade relative to those that do not plays a key role in the Balassa-Samuelson explanation of why countries' exchange rates differ systematically from their currencies' purchasing power. The B-S analysis leads to the proposition that the tradablenontradable price difference is lower for rich countries than for poor. This paper examines the gap, using prices collected by the International Comparison Programme. A variety of regressions were run to sce i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…Heston, Nuxoll and Summers (1994) found that the difference between tradable and non-tradable prices moved with the income levels of OECD countries, which is consistent with the results of Canzoneri, Cumby and Diba (1999). According to Tille (2001), productivity developments accounted for 2/3 of the US dollar's appreciations against the Euro and 3/4 of its appreciation against the Japanese yen in the nineties.…”
Section: Discussionsupporting
confidence: 90%
“…Heston, Nuxoll and Summers (1994) found that the difference between tradable and non-tradable prices moved with the income levels of OECD countries, which is consistent with the results of Canzoneri, Cumby and Diba (1999). According to Tille (2001), productivity developments accounted for 2/3 of the US dollar's appreciations against the Euro and 3/4 of its appreciation against the Japanese yen in the nineties.…”
Section: Discussionsupporting
confidence: 90%
“…35 Some other recent empirical evidence exists, however, in favor of the HarrodBalassa-Samuelson hypothesis. Heston, Nuxoll, and Summers (1994) examine the tradable-nontradable price differential across countries on the basis of the PURCHASING POWER PARITY AND THE REAL EXCHANGE RATE 91 33 An alternative underlying theory that also leads to the Harrod-Balassa-Samuelson hypothesis is due to Kravis and Lipsey (1983) and Bhagwati (1984), who build an imperfect capital mobility model and hence use the assumption that capital-labor ratios are higher in fast-growing countries relative to slowgrowing countries. For a comprehensive overview of the theoretical contributions and the empirical evidence on the Harrod-Balassa-Samuelson effect, see Asea and Corden (1994).…”
Section: = T N Purchasing Power Parity and The Real Exchange Ratementioning
confidence: 99%
“…Therefore the relative slower rate of growth in the non-traded goods sector results in higher relative nontraded goods' prices 2 . One prediction of this model is that the tradable-nontradable price difference is lower for rich countries than for poor countries (see Heston et al, 1994). Another consequence is that if traded goods' productivity relative to non-traded goods' productivity is growing faster at home than abroad, then the home country should experience an appreciation of the real exchange rate 3 .…”
Section: Introductionmentioning
confidence: 99%